The Effects of Team Games and Tournament Integrated with STEM 3D Audio-Visual Kit for Enhancing Collaboration Skills and Learning Outcomes - Billa, Attika Salsa; Narulita, Erlia; Amalia, Rachma Fadhillah; Supeno, Supeno (FKIP Universitas Lampung, 2024)
Collaboration is one of the essential skills that students must have in the global era. With collaboration skills, students can interact in groups and take responsibility for solving problems, impacting learning outcomes. However, integrating collaboration skills in learning still challenges teachers and students. Therefore, it is necessary to pilot innovative learning media to promote collaboration skills in learning activities. This study examined the impact of using STEM-based 3D audio-visual protein synthesis kit box learning media on collaboration skills and learning outcomes. The study was conducted on SMA Negeri 1 Tanggul students, Jember Regency, East Java. The study used a pre-test and post-test control group design. The experimental class was treated using the TGT learning model with STEM learning media, while the control class applied traditional learning. This study used two types of groups, namely large groups and small groups, which aimed to determine the effect of the number of members in the group on collaboration skills. Based on the one-way ANOVA test analysis in the control and experimental classes, the research results obtained a sig < 0.05 with the hypothesis Ha rejected, which means there is a difference in collaboration skills between students in large and small groups. The one-way ANOVA test analysis results in the control and experimental classes obtained a sig < 0.05 with the hypothesis H0 rejected, which means there is a difference in student learning outcomes. Keywords: collaboration skills, learning outcomes, team games and tournaments (TGT).DOI: http://dx.doi.org/10.23960/jpmipa/v25i3.pp1151-1164